A promising Ag2S/poly-2-amino-1-mercaptobenzene open-top spherical core–shell nanocomposite for optoelectronic devices: A one-pot technique - Alkallas Fatemah H.; Rabia Mohamed; Trabelsi Amira Ben Gouider; Alrebdi Tahani A.; Elsayed Asmaa M. (Nanotechnology Reviews)
Herein, we have introduced a novel and promising optoelectronic device, the Ag2S/poly-2-amino-1-mercaptobenzene open-top spherical core–shell nanocomposite (Ag2S/P2AMB CS-nanocomposite), fabricated using cost-effective and scalable production techniques. This device demonstrates high potential in sensing photons with various energies across a broad spectrum region, ranging from near-IR to UV. The Ag2S/P2AMB CS-nanocomposite, with its unique bandgap of 1.7 eV, broad optical absorbance, estimated crystalline size of 69 nm, and open spherical nanoparticles, is a significant advancement in the field of optoelectronics. The fabricated thin film device can detect photons with energies from 1.7 to 3.6 eV, corresponding to the near-IR and UV regions. Its sensitivity is measured through parameters such as the produced photocurrent density (J ph), photoresponsivity (R), and detectivity (D). The device can generate a photocurrent of 0.025 mA/cm², based on the difference between J ph and dark current (J o) values. As the wavelengths increase from 340 to 730 nm, J ph decreases from 0.039 to 0.028 mA/cm². The responsivity (R) ranges from 0.4 to 0.36 mA/W, while the detectivity (D) varies from 0.91 × 108 to 0.82 × 108 Jones at a small bias voltage of 2.0 V. These promising values indicate that the fabricated optoelectronic device is highly sensitive to photons. Its efficient performance, simple preparation, and cost-effective techniques estimate it as a strong recommendation for industrial applications, ensuring its economic viability.